Luther on women a sourcebook - Karant-Nunn, Susan C. 1941-; Wiesner, Merry E. 1952-; NetLibrary, Inc (EBSCOhost eBook Collection, 2003)
This collection brings together a wide selection of Martin Luther's extensive writings on women, the vast majority of them translated into English for the first time. The book makes Luther's sermons, lectures, pamphlets, polemic writings, letters and informal 'table talk' accessible to English-speaking scholars, students and general readers